Estudo psicanalítico sobre a feminização da epidemia do HIV/AIDS com usuários do Hospital Universitário João de Barros Barreto - LEBREGO, Arina Marques (Universidade Federal do Pará, 2014)
This study aimed to investigate the processes of subjectivation of women having no steady partners and their exposition to HIV/AIDS in order to identify overdetermination factors of vulnerability. As method, we used a case study, aiming at a in-depth analysis which allowed the identification of a greater number of subjective determinants related to the problem considered. The study presents fragments of clinical cases of women living with AIDS, hospitalized in the wards of the João de Barros Barreto University Hospital (HUJBB) in the State of Pará, Brazil. Based on the analysis of transference and countertransference, we showed as results what each case, in its singularity, reveals from the therapeutic encounter. In clinical case I, we found that the patient, whom we called Dinah, had a female masochistic mode of psychopathological subjectivation, what caused her to show some satisfaction when exposed to suffering, and to position herself as a victim in her emotional and sexual relationships. Those relationships were overdetermined by a imaginary identification with cultural ideals about the woman human being, conceiving images of men and women, and therefore of herself and her partners, as antithetical pairs of strength/weakness, active/passive, power/submission. This ideal of composite person of a virgin woman and a man only, caused Dinah to deny her fears of contamination, and to passively accept unprotected sexual relations, leaving the sexual initiative to her partner, and, thereby, becoming vulnerable to HIV infection. In clinical case II, Alice, which has a melancholic, self-destructive mode of subjectivation, positioned herself in her emotional and sexual relationships by incessantly searching for her self-destruction through an unconscious vulnerability to HIV. Having contracted AIDS and infected her husband and other partners, even after knowing her diagnosis, Alice remained trapped in a deadly silence, and prevented herd]self from taking care of her health and seeking continuous medical care, making herself vulnerable to re-infection. In clinical Case III, Ana Laura, is a woman who has gone through violence several times since childhood, for instance, she underwent child sexual abuse, was exploited as a domestic worker, was abandoned by her parents. After having her first baby, the child was taken from her without her consent by a maternal aunt who gave her to others. Ana Laura used that as a reason to prostitute herself on quay of Belém Port, where she worked until she was hospitalized. That was where negotiation for more expensive unprotected sex was a common practice, and so Ana Laura negotiated her life, selling unprotected sex and ended up getting infected by HIV. The helplessness and the violence that this patient went through are therefore the overdetermination factors of her vulnerability to HIV infection. As conclusions, we highlight that the women looked after without steady partners, did not care to protect themselves, and are not in accordance with the studies showing that those women negotiate the use of condom more freely and are less vulnerable to HIV. This demonstrates the importance of studies addressing the psychic, social, political and cultural aspects, so as to reveal the modes of production of subjectivity of the subjects in their singularity, beyond data measurement, in order to establish strategies for more effective health prevention.